PENERAPAN MODEL TGT (TEAMS GAMES TOURNAMENT) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA TEMA BENDA DI SEKITARKU SUBTEMA 1 PB 5 DI KELAS III SDN 105322 DESA MESJID T.P. 2022/2023 - Irena Br Barus (Universitas Pahlawan Tuanku Tambusai, 2022)
The use in this study is the TGT (Teams Games Tournament) Learning Model. This study aims to: Evaluate the learning outcomes of students who use the TGT Learning Model (Teams Games Tournament) on learning outcomes Theme Things Around Me Sub-theme 1 Pb 5 in Class III SDN 105322 Desa Mesjid T.P. 2022/2023. This type of research is an experiment with the subject of all class III students at SDN 105322 Masjid Village. The object of research was carried out by all class III students at SDN 105322 Desa Mesjid using the TGT (Teams Games Tournament) Learning Model. The instrument used in this study was a learning outcomes test in the form of 10 questions with details of 5 multiple choice, 2 entries and 3 matchmaking. From the results of the research, the average pre-test score was 39.13% of students completed, after the action was taken in the class, it was obtained that the Post Test Cycle I score was 60.86% students completed, and the Post Test Cycle II score was 86.95% students completed . Based on the results of the analysis above, it can be interpreted that using the TGT (Teams Games Tournament) Learning Model improves student learning outcomes with the theme Things Around Me sub-theme I pb 5 in class III SDN 105322 Desa Mesjid T.P. 2022/2023. Keywords: Learning Outcomes, TGT, Learning model